The effect of inlet temperature and pump flowrate of 5% carboxymethyl cellulose (CMC) in spray drying - Misni, Muhammad Zaidi (2017)
Carboxymethyl Cellulose (CMC) is cellulose derivative with carboxymethyl group attached to some of the hydroxyl group of glucopyranose monomers that make up cellulose backbone. CMC often used as sodium Carboxymethyl Cellulose because it’s easy for transportation compared to CMC in liquid form. Spray drying technology has massive potential over that of dehydration process especially in food and beverages industry. Spray drying has ability to produce high quality powder without changing any of its chemical compounds. The objective for this research is to study the effect of inlet temperatures of CMC spray drying towards solubility, pH, moisture content and powder recovery of the particles and to study suitable spray drying condition for maximum powder recovery. Although there are many research regarding of CMC properties but there is still can be elaborate more especially 5% CMC in spray drying.